2015
DOI: 10.1063/1.4922467
|View full text |Cite
|
Sign up to set email alerts
|

The influence of amino group on PCDTBT-based and P3HT-based polymer solar cells: Hole trapping processes

Abstract: Polymer solar cells (PSCs) based on aliphatic-amino-functionalized materials presented low performance with negligibly small efficiency, the prime mechanism of which is found to be hole trapping induced by the amine end groups. We propose that such hole trapping behavior depends on the relative energetic position of the hole transport states and the trapping states. Herein, we comparatively study the photovoltaic properties of PSCs based on amino-functionalized fullerene derivative blended with poly [N-9′-hept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
(37 reference statements)
0
14
0
Order By: Relevance
“…Upon applying a thin layer of TPD (3 nm), the V OC was marginally improved to 0.34 V, leading to an efficiency of 0.13%. Although the devices based on TQ1A showed photovoltaic response, the PCE is much lower compared to that of TQ1:PC 61 BM devices (Kroon et al, 2012), which could be due to the charge traps formed by the amino groups, indicated from the electrochemistry results (Cai et al, 2015).…”
Section: Polymermentioning
confidence: 86%
See 4 more Smart Citations
“…Upon applying a thin layer of TPD (3 nm), the V OC was marginally improved to 0.34 V, leading to an efficiency of 0.13%. Although the devices based on TQ1A showed photovoltaic response, the PCE is much lower compared to that of TQ1:PC 61 BM devices (Kroon et al, 2012), which could be due to the charge traps formed by the amino groups, indicated from the electrochemistry results (Cai et al, 2015).…”
Section: Polymermentioning
confidence: 86%
“…It has been previously reported that amino groups are potential hole traps in the BHJ devices containing aminefunctionalized active materials, due to that the highest occupied molecular orbital (HOMO) level of p-type polymer lies below the oxidation state of amine (Cai et al, 2015). Hence, electrochemistry was also performed on triethylamine to compare its oxidation process with amine-functionalized TQ1A.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations